2013
DOI: 10.1155/2013/303982
|View full text |Cite
|
Sign up to set email alerts
|

A Machine-Learned Predictor of Colonic Polyps Based on Urinary Metabolomics

Abstract: We report an automated diagnostic test that uses the NMR spectrum of a single spot urine sample to accurately distinguish patients who require a colonoscopy from those who do not. Moreover, our approach can be adjusted to tradeoff between sensitivity and specificity. We developed our system using a group of 988 patients (633 normal and 355 who required colonoscopy) who were all at average or above-average risk for developing colorectal cancer. We obtained a metabolic profile of each subject, based on the urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Eisner et al (22) performed urinary metabolomics in search of such a predictor and reported that nicotinate and nicotinamide metabolites and the degradation of ketone bodies are associated with the presence of CP. They proposed a tool involving the use of urinary metabolomics to select patients at risk of CP, who would undergo further investigation with colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eisner et al (22) performed urinary metabolomics in search of such a predictor and reported that nicotinate and nicotinamide metabolites and the degradation of ketone bodies are associated with the presence of CP. They proposed a tool involving the use of urinary metabolomics to select patients at risk of CP, who would undergo further investigation with colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal occult blood testing is intended to select patients with colorectal cancer, rather than pre-cancerous CP (24). Eisner et al (22) analyzed fecal occult blood testing as a tool for the detection of CP. Fecal occult blood testing has been shown to have a sensitivity of 2.6-15.1% and a specificity of 94.5-99.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with adenomatous polyps, a precursor of CRC, can be identified with a sensitivity of 64% and specificity of 65% using a machine learning algorithm to analyse 1 H-NMR spectroscopic profiles. 97 Studies associating the faecal metabolome with CRC have also been performed, but owing to the temporal and local variability in faecal composition, the number of participants required to generate meaningful conclusions is large. 98 Faecal samples from patients with CRC (n = 11) differed from healthy individuals (n = 10) in relative concentrations of fructose, linoleic acid, nicotinic acid.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…This study used NMR spectra acquired from 988 urine samples previously obtained as part of a regional colon cancer screening program in Edmonton, Canada (SCOPE ® , Stop Colorectal Cancer through Prevention and Education) [17][18][19]. Study participants of average or increased colorectal carcinoma risk were recruited.…”
Section: Study Participants and Urine Collectionmentioning
confidence: 99%